Argon impurity transport studies at Wendelstein 7-X using x-ray imaging spectrometer measurements. (14th June 2017) - Langenberg, A.; Pablant, N.A.; Marchuk, O.; Zhang, D.; Alonso, J.A.; Burhenn, R.; Svensson, J.; Valson, P.; Gates, D.; Beurskens, M.; Wolf, R.C.
Abstract: In the first operational phase of the stellarator Wendelstein 7-X (W7-X), the x-ray imaging crystal spectrometer (XICS) system has been commissioned for measuring radial profiles of ion and electron temperature, T i and T e, plasma rotation velocities, v P, and selected impurity densities, n Z . This paper shows the first measurements of the spectrometer and gives an initial calculation of impurity transport parameters derived from an Ar impurity transport study. Using Bayesian analysis, the temporal evolution of Ar impurity density profiles after an Ar gas puff could be observed with a time resolution of up to 5 ms, yielding a maximum value for the diffusion coefficient of D   =  1.5 m 2 s −1 at ρ ~ 0.5 and small pinch velocities in the inner plasma region.